2022
DOI: 10.1172/jci156863
|View full text |Cite
|
Sign up to set email alerts
|

A transcription factor is the target of propranolol treatment in infantile hemangioma

Abstract: Propranolol is a nonselective β-adrenergic receptor (AR) blocker that has been the first-line therapy for problematic infantile hemangioma (IH), the most frequent childhood vascular tumor. Although IHs are benign and eventually regress spontaneously, at least 15% of patients require treatment. Despite the extensive use of propranolol for IH treatment, its mode of action remains unclear. In this issue of the JCI , Seebauer et al. investigated the cellular and molecular consequences of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Propranolol is now known to be effective in treating non‐cardiovascular and cardiology disorders including hypertension, arrhythmias, migraine, and anxiety 7–11 . Although propranolol has been proven to be safe and effective in treating various diseases, 12 it must be noted that propranolol has two stereoisomeric forms, 13,14 both with differing medicinal effect on patients 15,16 . These effects include the drug's ability to reach the target site in a timely and accurate manner, as well as its rate of release without unwanted spreading to other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Propranolol is now known to be effective in treating non‐cardiovascular and cardiology disorders including hypertension, arrhythmias, migraine, and anxiety 7–11 . Although propranolol has been proven to be safe and effective in treating various diseases, 12 it must be noted that propranolol has two stereoisomeric forms, 13,14 both with differing medicinal effect on patients 15,16 . These effects include the drug's ability to reach the target site in a timely and accurate manner, as well as its rate of release without unwanted spreading to other areas.…”
Section: Introductionmentioning
confidence: 99%
“… 1 IHs appear shortly after birth and exhibit a unique life cycle characterized by rapid growth during the first 9–12 months, followed by slow and spontaneous regression. 2 , 3 Complications, including obstruction, dysfunction, ulceration, and disfigurement, occur in approximately 10% of patients. 4 Site-specific IHs can cause significant problems, such as organ failure, visual impairment, limited joint movement, respiratory distress, and death.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanism of action remains uncertain, it's believed that P acts by inhibiting vasoconstriction and angiogenesis in endothelial cells, leading to apoptosis (15). Additionally, recent studies have indicated that P hinders the differentiation of hemangioma stem cells into hemangioma endothelial cells (17). Most cases experience complete resolution, with response rates reaching up to 100% (15,18).…”
Section: Introductionmentioning
confidence: 99%